Memória social do bairro de Jardim da Penha do município de Vitória-ES - Oliveira, Priscila Silva de (2018)
Based on studies of the psychosocial perspective of memory, this research investigated the social memory of the suburb of Jardim da Penha in the city of Vitória-ES, built by residents, regarding 1970s and 1980s. The methodology, which included the qualitative analysis of three different datasets, uses a multi-method approach, with two main studies: historical memories (documentary and oral) and generational memory. The study of historical memories was carried out with documentary sources and with the application of in-depth individual interviews with seven key informants of leadership who acted in the 1970s and 1980s in the institutions considered as "places of memory" of the suburb: Religious Community, AMJAP and Clube 106. Specifically, the objective was to describe the history of the formation of Jardim da Penha in this period and to know “places of memory” of the suburb that helped to build social memories. Concerning the instrument, three different interview scripts were divided into three parts. The first one refers to the characterization of the participants. The second covers questions directed to the historical process of urbanization of Vitória-ES and Jardim da Penha. The third is related to the thematic axis that guided the research for each institution. The documentary material and interviews were compared and analyzed together, forming a corpus of data. The technique of content analysis was applied in order to apprehend the senses collectively developed in the historical memories of the suburb. The results indicated communitarian and solidary modes of sociability that expressed political movements in the improvement of the suburb. In the second methodological approach, that is, in the study of generational memory, the objective was to identify and describe the social memory of Jardim da Penha, built by three 21 generations of residents regarding 1970s and 1980s; to investigate the social construction of the memories of the suburb by people who did not live in the 1970s and 1980s but who had information from that time through others; and identify how the residents represented their territory in order to think about the processes of urban social identification. Three generational cohorts were interviewed: subjects aged 65 to 80 years (elderly); from 40 to 55 years (adults); and from 15 to 30 years (young people). Thirty residents (10 from each generational subgroup), who lived in the suburb for at least two years, participated. The technique used for the data collection was an individual in-depth interview based on a script divided into three parts. The first one collected sociodemographic data and the second and third identified memories and descriptive elements of Jardim da Penha in the past and present. The content generated in the 30 interviews was analyzed according to the thematic content analysis technique and allowed the grouping of narratives into four categories: Belonging, Contrasts, Diversity and Functionality. The results indicated that while elderly participants, based on their own experience, interpret the past of the suburb with a greater aspect of affective belonging, younger ones evoke their memories based on what they were told by their elders and give to the suburb an attribute of functionality. The contrasts category prevailed among adults aged 40 to 55 years. Despite being less frequent, the diversity category was shared by the three generations. The results suggest an affective dimension that mediates the relationship of the residents with their territory and constructions of "what a resident of Jardim da Penha is", based on the transmissions among generations and on the ways of living and relating to and in the suburb. A social representation of the suburb was also identified as a "pleasant and attractive place", which works to maintain the 22 group identity of the residents, and which is anchored in the social memories of the suburb. Both studies show that the social memory of Jardim da Penha, regarding 1970s and 1980s, anchors socio-spatial representations and identity processes of belonging. The shared affective field is related to the senses of community, solidarity, and family in Jardim da Penha, which have been interfering with the modern development of the suburb.